A new cost efficiency measure for not-for-profit firms: Evidence of a link between inefficiency and large endowments - Joseph P. Hughes (Rutgers University, Department of Economics, 2011)
Cost functions and cost efficiency are commonly estimated for industries with detailed data on production and cost, both for firms that are for profit as well as not for profit. The data on not-for-profits obtained from the IRS Form 990 lack these details and, consequently, encourage substitution of the ratio of program expenses to total expenses to gauge performance. While a larger program expense ratio captures better administrative cost efficiency, it does not gauge best-practice cost and the extent to which an organization's administrative costs exceed best practice. Using the Form 990 data, this study constructs an administrative cost function for not-for-profits and uses the distribution-free technique of estimating a best-practice cost frontier to gauge the relative efficiency of not-for-profit organizations. Focusing on not-for-profit hospitals and their holdings of liquid assets, the empirical evidence is consistent with Jensen's free cash flow hypothesis: hospitals holding liquid assets in excess of a benchmark have lower program expense ratios and lower cost efficiency. In addition, the CEOs of more cost efficient hospitals earn higher compensation. The agreement of the evidence on agency problems related to excess holdings of liquid assets from the program expense ratio and administrative cost efficiency reinforce the credibility of the latter as a measure of the performance of not-for-profit organizations.
Keywords: D24; D22; 330; not-for-profit; cost efficiency; free cash flow hypothesis